Feasibility study of a 4-DOF cable-driven exosuit for elbow and wrist rehabilitation - Alapati, Sreejan; Seth, Deep; Nakka, Sanjeevi; Aoustin, Yannick (Multibody system dynamics, 2025)
Cable-driven exosuits are emerging as an effective solution for upper limb rehabilitation, offering lightweight, flexible, and customizable assistance. While prior research for upper limb rehabilitation has primarily focused on single-joint actuation or systems with up to 2 degrees of freedom (DOF), the combined actuation of the elbow and wrist, including forearm pronation-supination, within an exosuit remains largely unexplored. Addressing this gap, this study investigates the feasibility of a 4-DOF cable-driven exosuit designed to assist these joints, which are essential for rehabilitation exercises and activities of daily living (ADLs) such as eating and object manipulation. A torque-tension model is developed to establish the relationship between joint torques and cable tensions. An optimization framework is implemented to determine optimal tension values. Motion capture data from six healthy subjects performing rehabilitation and daily tasks are used to analyze tension variations and validate the model. The results confirm that the proposed exosuit can provide effective assistance for the elbow and wrist while maintaining cable tensions optimized between 5 N to 50 N for ADLs. Furthermore, workspace analysis confirms that the exosuit maintains 100% feasibility across the rehabilitation range of motion. These insights lay the groundwork for an adaptive, personalized exosuit capable of assisting multi-DOF upper limb movements.